O crescimento não uniforme da geração distribuída no Brasil sob a óptica da nova economia institucional: uma análise comparativa entre o Paraná e Minas gerais - Galvão, Rodrigo Regis de Almeida (2021)
Distributed Generation (DG) plays an important role in the diversification of the energy matrix, in the decentralization of investments in energy generation and in the decarbonization of the environment, mainly because its sources are predominantly renewable. This characteristic is in line with the energy transition process that completely changes the way of planning the future of the electricity sector, especially in relation to its interaction with the final consumer, who, with the possibility of generating their own energy, starts to have a role active within the system. This, in turn, remarkably broadens the possibilities for business models. In Brazil, DG grows considerably, although not uniformly in the federative states. This non-uniformity is mainly due to the institutional environment created by each state, which consequently reduces organizational failures and transition costs. This is evident in the comparative results between the states of Minas Gerais and Paraná. It is known that the massive insertion of GD can bring benefits that go beyond the electricity sector, such as the creation of local service companies, technological suppliers, technological innovation startups, job creation, income and taxes. These results improve social and environmental indices and, consequently, contribute to sustainable economic development. It is estimated that for each megawatt installed per year, approximately 30 direct jobs and 90 indirect jobs will be created, in addition to reducing 3.5 million equivalent tons of CO2 in the atmosphere. This work aims to describe the institutional environment of DG in Brazil and in the states of Minas Gerais and Paraná, from the perspective of the New Institutional Economy and analyze, through a comparative methodology, the influence of state actions on non-uniform growth in the country. The results observed confirm the position that the institutional environment influences economic development and, in the case of DG, it had an impact on the attraction of investments, on the development of the business chain of services and products, in addition to not impacting the ICMS collection of distributors of energy with created incentives.